Demographic Changes in Different Agro-climatic Regions of Rajasthan - Gupta, B S; Chand, Roop; Gupta, K N (Annals of Arid Zone, 2025)
This research paper establishes the relationship between spatial distribution of population with its demographic characteristics. Based on 1991 primary population census, significant variations exist in the density of population and population growth rate in different agro-climatic regions, viz., arid, transitional between arid and semi-arid, semi-arid, subhumid and humid regions. Proportion of main workers and marginal workers to total population in different agro-climatic regions has also been dealt with. Main findings of some denlograpic characteristics in the agro-climatic regions are depicted through two tables and three maps at 1:25,000,00 scale.